2021
DOI: 10.1186/s12870-021-02868-z
|View full text |Cite
|
Sign up to set email alerts
|

MaMAPK3-MaICE1-MaPOD P7 pathway, a positive regulator of cold tolerance in banana

Abstract: Background Banana is a tropical fruit with a high economic impact worldwide. Cold stress greatly affects the development and production of banana. Results In the present study, we investigated the functions of MaMAPK3 and MaICE1 involved in cold tolerance of banana. The effect of RNAi of MaMAPK3 on Dajiao (Musa spp. ‘Dajiao’; ABB Group) cold tolerance was evaluated. The leaves of the MaMAPK3 RNAi transgenic plants showed wilting and severe necrotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 71 publications
(57 reference statements)
1
13
0
Order By: Relevance
“…We found that the expression of these four genes was lower in MdARF17 RNAi plants under cold stress as compared to GL‐3 plants (Figure 7), further suggesting MdARF17 regulates cold tolerance at least in part via CBF signaling. Homologs of MdCBFs , MdCCA1 , MdICE1 , MdZAT10 , MdCOR47 , MdWRKY33 , POD biosynthesis genes, and CAT‐related genes are positive regulators of cold tolerance, while the homolog of MdDGK1 is a negative regulator of cold stress tolerance (Chinnusamy et al., 2003; Du et al., 2008; Gao et al., 2021; Jaglo‐Ottosen et al., 1998; Medina et al., 2011; Seo et al., 2012; van Buer et al., 2019). We also detected the expression levels of cold‐responsive genes in MdmARF17 OE plants, and the results showed that cold‐responsive genes, including MdCBF1 , MdCBF2 , MdCBF3 , MdICE1 , MdCCA1 , MdCOR47 , MdWRKY33 , and CAT‐related genes ( MdCAT1 , MdCAT1‐like , and MdCAT2 ), were upregulated in MdmARF17 OE plants under cold conditions, as compared to GL‐3 plants (Figure S4), further suggesting MdARF17 positively regulates these genes under cold conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the expression of these four genes was lower in MdARF17 RNAi plants under cold stress as compared to GL‐3 plants (Figure 7), further suggesting MdARF17 regulates cold tolerance at least in part via CBF signaling. Homologs of MdCBFs , MdCCA1 , MdICE1 , MdZAT10 , MdCOR47 , MdWRKY33 , POD biosynthesis genes, and CAT‐related genes are positive regulators of cold tolerance, while the homolog of MdDGK1 is a negative regulator of cold stress tolerance (Chinnusamy et al., 2003; Du et al., 2008; Gao et al., 2021; Jaglo‐Ottosen et al., 1998; Medina et al., 2011; Seo et al., 2012; van Buer et al., 2019). We also detected the expression levels of cold‐responsive genes in MdmARF17 OE plants, and the results showed that cold‐responsive genes, including MdCBF1 , MdCBF2 , MdCBF3 , MdICE1 , MdCCA1 , MdCOR47 , MdWRKY33 , and CAT‐related genes ( MdCAT1 , MdCAT1‐like , and MdCAT2 ), were upregulated in MdmARF17 OE plants under cold conditions, as compared to GL‐3 plants (Figure S4), further suggesting MdARF17 positively regulates these genes under cold conditions.…”
Section: Resultsmentioning
confidence: 99%
“…RNA‐seq data revealed that MdARF17 positively regulates genes including MdCBF2 , MdZAT10 , MdCOR47 , MdCCA1 , MdICE1 , MdCBF1 , MdCBF3 , MdWRKY33 , MdPOD2 , MdPOD25 , MdCAT1 , MdCAT1‐like , and MdCAT2 , while it negatively regulates MdDGK1 (Figure 7). Homologs of MdCBF2 , MdZAT10 , MdCOR47 , MdCCA1 , MdICE1 , MdCBF1 , MdCBF3 , MdWRKY33 , MdPOD2 , MdPOD25 , MdCAT1 , MdCAT1‐like , and MdCAT2 are positive regulators of cold tolerance (Chinnusamy et al., 2003; Du et al., 2008; Gao et al., 2021; Jaglo‐Ottosen et al., 1998; Medina et al., 2011; Seo et al., 2012; Thomashow, 2001; van Buer et al., 2019), while a homolog of MdDGK1 is a negative regulator (Gómez‐Merino et al., 2004; Luo et al., 2004). Therefore, the effects of MdARF17 on cold tolerance can be attributed to the transcriptional regulation of these cold‐negative and cold‐positive factors.…”
Section: Discussionmentioning
confidence: 99%
“…CIPK3 and CIPK7 are two members that play a crucial role in cold stress signaling by positively regulating cold‐induced genes (Kim et al, 2003; Xiang et al, 2007). In addition, MAPK3 in rice and banana have been demonstrated to regulate cold tolerance by stimulating the expression of CORs (Zhang et al, 2017; Gao et al, 2021). LTI65 is a member of CBF regulon, suggesting its potential role in cold stress response.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it could not provide direct insight into the tolerance mechanism under field conditions. Gao et al (2021) analysed the transcriptome of MaMAPK 3 in 'Dajiao' with wild‐type Cavendish banana under cold. They reported that the transgenic lines having suppressed expression of MaMAPK 3 were highly cold sensitive compared to wild type.…”
Section: Genetic Engineering Mutagenesis and Transgenesis In Banana F...mentioning
confidence: 99%